Geotechnical instrumentation and monitoring in open pit and underground mining - Australian Conference on Geotechnical Instrumentation and Monitoring in Open Pit and Underground Mining (1993 : Kalgoorlie, Western Australia); Szwedzicki, T. (Rotterdam : AA Balkema, 1993)
51